Impact of crush syndrome severity on clinical outcomes after the earthquakes in southeastern Turkiye - Turgutalp, Kenan; Ozturk, Savas; Koc, Neriman Sila; Dolarslan, Murside Esra; Kocyigit, Ismail; Turgut, Didem; Tuglular, Serhan (Bmc, 2026)
Background: Crush syndrome is a potentially life-threatening complication of prolonged compression injuries, frequently encountered after earthquakes. The 2023 Kahramanmara & scedil; earthquakes in Turkiye caused extensive crush-related trauma. The objective of this study was to assess the effect of baseline crush syndrome severity on hospitalization outcomes and complications. Methods: In this multicenter, retrospective observational study, 962 crush syndrome patients hospitalized after the earthquakes were evaluated. Patients were grouped as mild-moderate vs. severe-critical based on clinical presentation. Demographics, laboratory results, comorbidities, trauma types, complications, and outcomes were assessed. Comparisons between groups were performed using the Mann-Whitney U test and chi-square test, and survival analysis was conducted with the Kaplan-Meier method. Results: Of 962 patients, 232 (24.1%) were classified as severe-critical and 730 (75.9%) as mild-moderate. Severe-critical patients had significantly higher rates of hypotension (38.8% vs 2.3%), ARDS (10.2% vs 1.7%), sepsis (31.7% vs 9.1%), DIC (8.5% vs 1.4%), arrhythmias (11.9% vs 0.8%), compartment syndrome (53.5% vs 36.9%), and ICU (95.6% vs 40.9%) requirement than mild-moderate (all p<0.001). Laboratory markers including BUN, creatinine, potassium, phosphorus, liver enzymes, CK, and CRP were all significantly elevated, while calcium and albumin levels were lower in the severe-critical group (p<0.05). Kaplan-Meier analysis revealed a significantly lower survival rate in the severe-critical group (67.7% vs. 97.7%, p<0.001). Trauma types such as cranial, abdominal, and thoracic injuries were more frequent in this group, and prolonged entrapment time [median 18 (8-40) vs. 10 (6-33) hours, p<0.05] was correlated with increased severity. Conclusions: Crush syndrome severity at admission is strongly correlated with clinical outcomes, complication rates, and in-hospital survival. Prolonged time under the rubble, systemic complications, and elevated muscle and renal injury markers contribute to worse prognosis. These findings highlight the need for rapid triage, timely fluid resuscitation, and organized multidisciplinary intervention in future disaster scenarios.
Keywords: Crush syndrome; Earthquakes; Acute kidney injury; Rhabdomyolysis; Southeastern Turkiye